The Effect of Papain Enzyme Concentration on Protein Content and Antioxidant Activity of Skipjack Tuna (Katsuwonus pelamis) Protein Hydrolysate - Moleong, Rahel Syallomita; Fatimah, Feti; Kumajas, Jenny (Jurnal Beta Kimia, 2026)
Protein deficiency is one of the most common nutritional problems found in Indonesia. Skipjack tuna is a source of high-quality protein; however, it is highly perishable and therefore requires processing to extend its shelf life. One alternative processing method is the production of protein hydrolysates, which also possess antioxidant activity; nevertheless, optimization of enzyme concentration is required to obtain protein hydrolysates with optimal characteristics. This study aims to analyze the effect of variations in papain enzyme concentration on protein content and antioxidant activity of skipjack tuna protein hydrolysates, where the hydrolysis process was carried out using papain enzyme concentrations of 4%, 5%, and 6% at a temperature of 55°C for 2 hours, and the research data were statistically analyzed using analysis of variance (ANOVA) to determine differences among treatments. Protein content was determined using the Kjeldahl method, while antioxidant activity was analyzed using the DPPH free radical scavenging assay. The results of protein content analysis showed the best value at an enzyme concentration of 6% at 1.22%, and the results of the antioxidant activity test showed the highest value of 66.04% at an enzyme concentration of 6%; in conclusion, an increase in enzyme concentration affects the increase in protein content and antioxidant activity of the hydrolysate, and these findings indicate that optimizing papain enzyme concentration is important in producing skipjack tuna protein hydrolysates with better functional characteristics, thus having the potential to be developed as a functional food ingredient.